2013
DOI: 10.1074/jbc.m112.439828
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of GDP-fucose and Other Sugar Nucleotides in the Blood Stages of Plasmodium falciparum

Abstract: Background: GDP-fucose and other sugar nucleotide biosynthetic pathways are conserved in the P. falciparum genome. Results: These pathways are active in the intraerythrocytic life cycle of the parasite. Conclusion:The parasite biosynthesizes GDP-fucose and other sugar nucleotides not related to the glycosylphosphatidylinositol structures Significance: Their presence strongly suggests that they are involved in the biosynthesis of glycans not yet characterized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
53
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(56 citation statements)
references
References 74 publications
3
53
0
Order By: Relevance
“…Glycosyltransferase activity and sugar nucleotides donors have long been linked to protein folding and thermotolerance in many organisms, including different parasites353637. It has been suggested that Protein O -fucosyltransferase 2 (PoFUT2), of which a homolog is conserved and expressed in the P. falciparum genome18, may be involved in a novel quality control mechanism for the proper folding of TSR-domain containing proteins in the endoplasmic reticulum (ER)3738. Proteins with TSR-domains have been shown to be expressed in asexual stages and to be involved in host-cell invasion3940.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Glycosyltransferase activity and sugar nucleotides donors have long been linked to protein folding and thermotolerance in many organisms, including different parasites353637. It has been suggested that Protein O -fucosyltransferase 2 (PoFUT2), of which a homolog is conserved and expressed in the P. falciparum genome18, may be involved in a novel quality control mechanism for the proper folding of TSR-domain containing proteins in the endoplasmic reticulum (ER)3738. Proteins with TSR-domains have been shown to be expressed in asexual stages and to be involved in host-cell invasion3940.…”
Section: Resultsmentioning
confidence: 99%
“…A C18 reversed-phase column was used for sugar nucleotide separation with a gradient from 0.5% to 4% acetonitrile in 20 mM triethylammonium acetate buffer over 20 min at a flow rate of 25 µl/min. Sugar nucleotides were identified by their diagnostic MRM transitions18. The peak areas for each sugar nucleotide, along with their empirically determined molar relative response factors and the known amount of internal GDP-Glc, were used to quantify sugar nucleotides.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…gondii Nuclear Fucosylation Is Dependent on the de Novo GDPFucose Biosynthetic Pathway. Because T. gondii and other apicomplexans have no salvage pathway for fucose (25,26), GDPfucose is synthesized from GDP-mannose in a three-step process catalyzed by GDP-mannose dehydratase (GMD, TGGT1_238940) and GDP-fucose synthase (Fig. S2D) (21).…”
Section: Significancementioning
confidence: 99%
“…Even so, homologs of several genes required for protein glycosylation are present and conserved in the genomes of Plasmodium spp. and metabolomic analyses of parasite material has demonstrated the presence of the nucleotide sugars required for protein glycosylation, which alluded to the existence of as yet undiscovered parasite glycans.With the aid of modern protein mass spectrometry methods, several research groups have recently tackled the issues of glycan lability and relatively small sample sizes to begin characterizing the true diversity of Plasmodium protein glycosylation [6][7][8][9][10][11][12]. Evidence for the synthesis of short N-linked glycans has been reported in asexual blood stages of Plasmodium falciparum [6], and there is every reason to expect that these modifications will be found in other life cycle stages as well.…”
mentioning
confidence: 99%